UNwilling or UNable? The United Nations and the recurrent problem of sexual abuse - Egelström, Sandra (Nordisk Tidsskrift for Kriminalvidenskab, 2021)
Abstract Since its establishment in 1945, the United Nations has grown to become a powerful intergovernmental body enjoying respect and legitimacy among a large part of the international community. Unfortunately, since the 1990s there have been recurrent problems with the organization’s peacekeeping forces being accused of sexual violence against the very people they are supposed to protect. In this article, the UN’s management of events in the Central African Republic (CAR) in 2014 and its inability to put an end to the sexual assaults committed by its representatives have been used to explore whether the organization could be accused of a state crime – under the presumption that the UN can be equated with a state. To do this, the definition of state crime and the complicity continuum developed by Kauzlarich, Mullins and Matthews (2003) are used to evaluate the UN’s actions in relation to the events in the CAR. The responsibilities of the UN in situations like the one in the CAR are examined and discussed. Abstract Förenta nationerna har sedan starten 1945 utvecklats till en mäktig mellanstatlig organisation som åtnjuter respekt och legitimitet från majoriteten av det internationella samfundet. Dessvärre har det, sedan 1990-talet, vid upprepade tillfällen uppdagats att organisationens fredsbevarande styrkor anklagats för sexuellt våld mot just de grupper som de är satta att beskydda. I denna artikel användes organisationens hantering av händelserna i Centralafrikanska republiken (CAR) under 2014, samt dess oförmåga att stoppa sexuella övergrepp utförda av dess företrädare, för att undersöka om FN kunde anklagas för en statligt brott, under förutsättning att organisationen kan likställas med en stat. För detta användes Kauzlarich, Mullins och Matthews (2003) definition av statlig brottslighet, samt det complicity continuum som de utvecklat, för att utvärdera FN:s åtgärder under händelserna i CAR. FN:s ansvar i situationer som det i CAR problematiseras och diskuteras.